Degradable Vinyl Random Copolymers via Photocontrolled Radical Ring‐Opening Cascade Copolymerization. Issue 8 (11th January 2022) - Wang, Wenqi; Zhou, Zefeng; Sathe, Devavrat; Tang, Xuanting; Moran, Stephanie; Jin, Jing; Haeffner, Fredrik; Wang, Junpeng; Niu, Jia
Abstract: Degradable vinyl polymers by radical ring‐opening polymerization are promising solutions to the challenges caused by non‐degradable vinyl plastics. However, achieving even distributions of labile functional groups in the backbone of degradable vinyl polymers remains challenging. Herein, we report a photocatalytic approach to degradable vinyl random copolymers via radical ring‐opening cascade copolymerization (rROCCP). The rROCCP of macrocyclic allylic sulfones and acrylates or acrylamides mediated by visible light at ambient temperature achieved near‐unity comonomer reactivity ratios over the entire range of the feed compositions. Experimental and computational evidence revealed an unusual reversible inhibition of chain propagation by in situ generated sulfur dioxide (SO2 ), which was successfully overcome by reducing the solubility of SO2 . This study provides a powerful approach to degradable vinyl random copolymers with comparable material properties to non‐degradable vinyl polymers. Abstract : A general approach to degradable vinyl random copolymers via photocontrolled radical ring‐opening cascade copolymerization (rROCCP) is developed. A variety of acrylates or acrylamides can be copolymerized with the macrocyclic allylic sulfone with near‐unity comonomer reactivity ratios at all feed compositions. The unusual reversible inhibition of chain propagation by sulfur dioxide in rROCCP was resolved by reducing the solubility of sulfur dioxide.